Data-driven leaf pruning based on weekly light integral: importance of dynamic defoliation strategy - Kim, Changhyeon; Kubota, Chieri (Frontiers in Plant Science, 2025)
IntroductionHigh-wire tomato production requires labor-intensive tasks such as clipping, suckering, and leaf pruning. Leaf pruning is essential for managing a balance between vegetative and reproductive growth of plants. Commercial practices involve maintaining a certain number of leaves or no leaves below harvesting trusses. However, an optimum timing of leaf pruning for saving labor demand and improving crop performance is not well characterized. MethodHere, we introduce a data-driven leaf pruning method, in which lower leaves were removed when weekly light integral (WLI) below canopy fell below a pre-determined WLI based on the lowest leaf’s light compensation point (LCP). The number of leaves to prune at a time was three and a minimum pruning interval was one week. Additionally, we evaluated two ranges of photosynthetically active radiation (PAR): PAR (400 – 700 nm) and ePAR (400 – 750 nm) for monitoring WLI below the canopy. We compared the new leaf-pruning method based on WLI PAR (in Experiments 1 and 2) and WLI ePAR (only in Experiment 2) to the conventional leaf-pruning method, in which leaves below harvesting trusses were removed followed by harvesting (Control). For the evaluation, indeterminate tomato cultivar ‘Maxxiany’ was grown in a Venlo-style greenhouse (482 m2 and 7-m gutter height) at a density of 3 plants m-2. Results and discussionRegardless of PAR range, the WLI-based pruning methods resulted in 35 - 42% fewer pruning events. The fewer pruning events were associated with the supplemental lighting use, leaving significantly more leaves per plant in the WLI-based pruning method than in Control. No significant differences were observed in the weekly increase in stem length, the stem diameter, and the cumulative yields between WLI-based pruning method and Control. However, WLI-based pruning method increased the total soluble solid contents of the harvested fruit. These findings suggest that: 1) Leaf pruning strategies should be adjusted based on light availability within the crop canopy, which is influenced by solar radiation and supplemental lighting, and 2) Monitoring WLI below canopy to determine leaf pruning timing is an effective method in lowering labor cost without reducing yield and fruit quality.